2015
DOI: 10.2174/1745017901511010102
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of School-Based Alcohol and other Drug Prevention Programs

Abstract: Background: Alcohol use in adolescents constitutes a major public health concern. Europe is the heaviest drinking region of the world. Several school-based alcohol prevention programs have been developed but it is not clear whether they are really effective. The present study was aimed at identifying the typology with the best evidence of effectiveness in European studies. Methods: A systematic search of meta-analyses and/or randomized controlled trials (RCTs) on interventions school-based prevention programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 95 publications
1
41
0
5
Order By: Relevance
“…A Cochrane review [21] of the effectiveness of universal alcohol abuse prevention programs for children and adolescents found that less than half of the included studies (43.4%) reported significant beneficial results. In a recent systematic review by Agabio et al [22] that included 12 randomized controlled trials not assessed in Foxcroft and Tsertsvadze’s study, 7 of these 12 additional reviewed interventions were more effective than control groups. However, a recent meta-analysis of reviews concluded that there was a small but consistent positive effect of school-based prevention programs; however, it is less clear what the “active ingredient” of such success is [23].…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review [21] of the effectiveness of universal alcohol abuse prevention programs for children and adolescents found that less than half of the included studies (43.4%) reported significant beneficial results. In a recent systematic review by Agabio et al [22] that included 12 randomized controlled trials not assessed in Foxcroft and Tsertsvadze’s study, 7 of these 12 additional reviewed interventions were more effective than control groups. However, a recent meta-analysis of reviews concluded that there was a small but consistent positive effect of school-based prevention programs; however, it is less clear what the “active ingredient” of such success is [23].…”
Section: Introductionmentioning
confidence: 99%
“…Such campaigns typically focus on improving the knowledge among school students of the harms associated with drugs early in the onset sequence, and delaying or preventing their use. There is emerging evidence that early secondary school‐based drug education may be efficacious (Agabio et al, ; Botvin & Griffin, ; Champion, Newton, Barrett, & Teesson, ; Champion et al, ; Koning, van den Eijnden, Verdurmen, Engels, & Vollebergh, ; McBride, Farringdon, Midford, Meuleners, & Phillips, ; Newton, Andrews, Teesson, & Vogl, ; Newton, Teesson, Vogl, & Andrews, ; Vogl et al, ). Such interventions have demonstrated increases in knowledge of substance‐related harm, a lower likelihood of consumption of early onset substances, and decreased intention to use these drugs (Champion et al, ; Newton et al, ; Vogl et al, ).…”
Section: Early Psychosocial Correlates Of Heroin Use and Possible Intmentioning
confidence: 99%
“…4 A recent systematic review exploring the effectiveness of universal school-based drug and alcohol prevention programs found that, worldwide, less than half produced significant, positive behavior changes. 1 Another review of U.S.-based school prevention programs targeting elementary school children, found a similar rate of effectiveness, with a little over half of the programs leading to positive behavior change. 3 The relatively low effectiveness of prevention programs is even more troubling given the largely homogenous study conditions in which most trials occur.…”
Section: Introductionmentioning
confidence: 95%
“…Adolescent drug and alcohol use is a major public health concern worldwide, and its prevention is the subject of numerous programmatic efforts. 1 The risks associated with substance use are well characterized, vary by substance, and range from increased risk of injury and violence exposure to increased risk of chronic diseases such as cancer and cardiovascular disease. 2 Importantly, early initiation of substance use is a known risk factor for later substance use disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation